A bio-inspired cellulose nanocrystal-based nanocomposite photonic film with hyper-reflection and humidity-responsive actuator properties. Issue 41 (10th October 2016) - Wu, Tianhang; Li, Jiada; Li, Juntao; Ye, Simin; Wei, Jie; Guo, Jinbao
Abstract : The hyper-reflection and humidity-responsive behavior of a bio-inspired cellulose nanocrystal-based nanocomposite photonic film are described. Abstract : We have developed a cellulose nanocrystal-based nanocomposite photonic film with a sandwich structure to mimic the shell structure of the Chrysina genus of beetles. The nanocomposite film was fabricated by embedding a uniaxially oriented polyamide-6 (PA-6) layer as a half-wave retarder layer between two cellulose nanocrystals (CNCs)/polyethylene glycol diacrylate (PEGDA) layers with a left-handed chiral nematic photonic structure. As a result, the reflectance intensity of the obtained nanocomposite film exceeds 50% (hyper-reflection) at a certain wavelength. More interestingly, asymmetric expansion/shrinkage of the CNCs/PEGDA layer in the nanocomposite film allows for simultaneous and reversible three-dimensional deformation behavior as well as the shift of the Bragg reflection when exposed to a humid environment. The proposed self-assembled photonic material will be attractive to be used as an optical anti-counterfeiting film, a tunable bandpass filter, a reflector or polarizer and a humidity-responsive actuator.